In vitro activity of cefiderocol against carbapenem-resistant Acinetobacter baumannii clinical isolates: a single center experience. - Matera, Giovanni (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Introduction: Cefiderocol (CFDC) is a novel siderophore cephalosporin with broad-spectrum activity against carbapenem-resistant Gram-negative bacteria. Gram-negative bacterial isolates’ resistance to cefiderocol (CFDC) is emerging in clinical practice.